Pharmacogenetics to Avoid Adverse Drug Reactions - López-Fernández, Luis A. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Adverse drug reactions are one of the major constraints when using drugs. These adverse reactions can impact healthcare systems as strongly as many prevalent diseases. Identifying DNA variants associated with adverse drug reactions can help personalize medicine and sustain healthcare systems. This book delves into new advances in pharmacogenetics of cardiovascular, cancer, and nervous system drugs. It may be useful for clinicians and patients to understand the basics of pharmacogenetics.